The Violent Aporia of Postcolonial Public Life: Environmental Politics and Indigenous Self-determination in the Amazon - Rafael Costa (e-cadernos ces)
Indigenous communities’ participation in environmental politics of dam projects in the Brazilian Amazon is marked by an ambivalent effect. On one hand, there is the local political economy regulated by traditional systems; on the other hand, there is the global political procedure addressed to ‘empower’ indigenous institutions in their interactions with corporate and governmental actors. Yet, when this second juridical instance is dominated by suspicion, due not only to the lack of execution of environmental compensating measures, but mainly to the lack of space where indigenous principles could be taken into account, official political systems are frequently undermined by local forms of representation, personified in the image of the ‘indigenous warrior’. This article seeks to reveal how the enactment of the warrior in Brazilian public life ends up redefining ethnic agency, not as a remaining cultural trait of a particular symbolic economy, but as crime.